Sounder - Armstrong, William H. James Barkley, illustrator (New York Harper & Row, 1969)
Angry and humiliated when his sharecropper father is jailed for stealing food for his family, a young black boy grows in courage and understanding by learning to read and through his relationship with his devoted dog Sounder.
Elementary
Newbery Award, 1970
Keywords: Armstrong, William H. -- African Americans- juvenile fiction -- African Americans- fiction -- Dogs- fiction -- Family life- fiction -- Poverty- fiction